2018
DOI: 10.3389/fsufs.2018.00010
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Urine Patches on Intensively Managed Grassland Using Aerial Imagery Captured From Remotely Piloted Aircraft Systems

Abstract: The deposition of livestock urine and feces in grazed fields results in a sizable input of available nitrogen (N) in these soils; therefore significantly increasing potential nitrogen pollution from agricultural areas in the form of nitrous oxide (N 2 O), ammonia (NH 3 ), and nitrate (NO 3 − ). Livestock deposition events contributes to high spatial variability within the field and generate uncertainties when assessing the contribution that animal waste has on nitrogen pollution pathways. This study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…According to Adhikari et al (2021) in intensively managed dairy pastures, urine deposited by cattle during grazing covers relatively small proportion of the total grazed area. Maire et al (2018) reported that urine patches represent only about 6-12% of the grazed area in a single dairy cow grazing event. Therefore, there is a large potential for limiting the risk of NIs entry into these systems if these compounds can be targeted directly to urine patches, avoiding the need for their application across often large areas of pasture unaffected by urine deposition during grazing.…”
Section: Application Of Nitrification and Urease Inhibitorsmentioning
confidence: 99%
“…According to Adhikari et al (2021) in intensively managed dairy pastures, urine deposited by cattle during grazing covers relatively small proportion of the total grazed area. Maire et al (2018) reported that urine patches represent only about 6-12% of the grazed area in a single dairy cow grazing event. Therefore, there is a large potential for limiting the risk of NIs entry into these systems if these compounds can be targeted directly to urine patches, avoiding the need for their application across often large areas of pasture unaffected by urine deposition during grazing.…”
Section: Application Of Nitrification and Urease Inhibitorsmentioning
confidence: 99%
“…Additionally, the increase number of samples added with the addition of new surveys will eventually allow the use of more automatically calibrated algorithms. This study isa step forward for a more precise, repeatable and reliable detection process compared to more subjective or manual detection methods employed in previous published research (Dennis et al, 2013;Jolly et al, 2019;Maire et al, 2018). Nonetheless, in remote sensing, other classification methods are available, such as random forest algorithms or convolution neural networks which, with a high number of input samples, can help to produce highly accurate algorithms to detect objects in images captured under diverse conditions (Thanh Noi & Kappas, 2017).…”
Section: Excreta Deposits Detection Using Rpas Imagerymentioning
confidence: 94%
“…The maps were created from a Remotely Piloted Aircraft Systems (RPAS) survey before and after each grazing period, to estimate the areas where urine or dung was deposited. The method employed for this experiment uses the grass response to the N input from urine and directly assesses the dung deposits through an object-based algorithm improved from Maire et al, (2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, new remote sensing techniques using high resolution cameras linked to unmanned aerial vehicles (UAVs) is allowing improved understanding of the spatial and temporal patterns of deposition associated with such livestock management. A recent study used image analysis to quantify the appearance of urine patches in an intensively grazed grassland in Scotland [19] . Previous studies have shown that such urine patches contribute to very high emissions of N 2 O, which vary throughout the growing season in response to climatic conditions [20,21] .…”
Section: Managing Organic Nitrogen Inputsmentioning
confidence: 99%